Molecular Stacking on Graphene. (5th July 2022) - Wei, Tao; Liu, Xin; Kohring, Malte; Al‐Fogra, Sabrin; Moritz, Michael; Hemmeter, Daniel; Paap, Ulrike; Papp, Christian; Steinrück, Hans‐Peter; Bachmann, Julien; Weber, Heiko B.; Hauke, Frank; et al.
Abstract: The sequential vertical polyfunctionalization of 2D addend‐patterned graphene is still elusive. Here, we report a practical realization of this goal via a "molecular building blocks" approach, which is based on a combination of a lithography‐assisted reductive functionalization approach and a post‐functionalization step to sequentially and controllably link the molecular building blocks ethylpyridine, cis ‐dichlorobis(2, 2′‐bipyridyl)ruthenium, and triphenylphosphine (4‐methylbenzenethiol, respectively) on selected lattice regions of a graphene matrix. The assembled 2D hetero‐architectures are unambiguously characterized by various spectroscopic and microscopic measurements, revealing the stepwise stacking of the molecular building blocks on the graphene surface. Our method overcomes the current limitation of a one‐layer‐only binding to the graphene surface and opens the door for a vertical growth in the z‐direction. Abstract : The first prototype of spatially defined graphene 2D hetero‐architectures bearing vertically aligned multiple molecular bricks is realized based on a proposed "molecular building blocks" concept. The constructed nano‐assemblies exhibit structural hierarchies across multiple height scales and versatile properties. The results represent a breakthrough and open the door for future construction of promising patterned 3D architectures.